(untitled) (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
This study describes the common blunders made by pupils when solving mathematical problems by applying Newman’s theory. A systematic literature review is employed in this study, which entails the following steps: (1) question formulation; (2) search strategy development; (3) data evaluation and analysis; and (4) interpretation and reporting of study findings. For this analysis, fifteen articles were considered. According to the findings, a lot of students need to work on their arithmetic problem-solving skills. According to Newman’s approach, there are five common mistakes that students make: not understanding, not reading, not transforming, not using process skills correctly, and not writing the answers. When dealing with mathematical issues, such as story problems, this is a common occurrence. Errors are typically caused by students’ lack of reasoning skills and originality when it comes to solving problems in real-world contexts and transforming them into algebraic form. First and foremost, it is critical that students develop a habit of appropriately using the problem-solving process